Standardization of Panchavaktra Rasa w.s.r to Rasa Prakash Sudhakara - Bairwa, Dhan Raj; Meena, Mohar Pal; Tare, Manish; Verma, Vijay Shankar (International Research Journal of Ayurveda & Yoga, 2022)
Rasashastra and Bhaishajya Kalpana is the most important branch of learning in the field of Ayurveda. To save the lives of ailing people physician should also have a thorough grip on the principles of the formulations and their practical application. With the art and skill of formulation, a poisonous drug can be transmuted into a safe and effective drug. A simple drug can be converted into a most potent one. Panchavaktra rasa (PR) had been mentioned in various literatures viz, Rasa Prakash Sudhakar, Ras ratna Sammuchaya, Yoga Ratnakara, Sharangadhara etc. in Jwara rogadhikara. The present research work entitled “Standardization of Panchavaktra rasa w.s.r to Rasa Prakash Sudhakara” was planned to standardize the formulations as per the reference of Rasa Prakash Sudhakara. The Samguna Gandhaka kajjali ,Maricha churna, Pippali Churna, Shuddha Vatsnabha churna, Shuddha Tankana churna were mixed and levigated with Dhatura patra swarasa for the formulation of Panchavakta Rasa.The samples were analyzed based on Organoleptic Parameters, i.e., Appearance, Colour, Odour, Taste and Physico-chemical Parameters i.e., pH Value, Loss on Drying, Ash Value, Acid insoluble Ash, Water Soluble Ash, Sulphated Ash, Alcohol Soluble Extractive, Water Soluble Extractive. The samples were analysed for standardization of vati parameters i.e., hardness of pills, friability test, disintegration time etc. Total bacterial count and Total fungal count are under the permissible limit depicted in the study. For qualitative analysis HPTLC & ICP-MS were done. The Samples were analysed on different wavelengths 510 nm, 366 nm (Long) & 254 nm (Short). PR1 Sample confirmed 10 distinct spots at 510 nm, 07 distinct spots at 366 nm and 09 spots at 254 nm whereas PR2 sample confirmed 11 distinct spots at 510 nm, 06 distinct spots at 366 nm and 08 spots at 254 nm. The PR3 sample confirmed 10 distinct spots at 510 nm, 07 distinct spots at 366 nm and 08 spots at 254 nm. The Rf values of spots differentiate the chemical composition of the sample.